DISCOVERING THE CLASSIFICATION OF MANUFACTURING COMPLEXITY FROM MALAYSIAN INDUSTRY PERSPECTIVE - Rosdi, M.N.H.M.; Mahmood, W.H.W.; Kamat, S.R.; Tukimin, R.; Ayuni, N.S. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Nowadays, manufacturing complexity (MC) is considered as a major challenge in manufacturing industry. MC covers a very wide area in manufacturing practices either within firm’s control or out of control, either directly or indirectly with manufacturing routines. As the technology and globalization getting better, the challenges born by MC are also getting tougher. This scenario experienced by worldwide manufacturing firms including Malaysian manufacturing industry. In order to face this challenges, it is essential to manage MC accordingly. Although some researchers expressed MC negatively, it is believed that managing MC in correct manners will be beneficial to manufacturing firms. The first step towards managing MC accordingly is knowing MC itself in every angle. Generally, MC is divided into two division which are internal MC (IM) and external MC (EM). Initially, both division have several elements which the numbers are 30 and 22 elements for IM and EM, respectively. A set of questionnaire survey consisting of these elements has been distributed to representative of manufacturing firms across Malaysia to gather the information and through factorial analysis using Statistical software (SPSS), these elements are classified into smaller number of classification to facilitate towards the better MC management. The classifications for IM are human management, production design, productivity, job floor management and conflicts while for EM are local culture, trend changes, volume variety and globalization. These classifications will support industrialist especially in Malaysia towards better MC management to grow a better outcome in manufacturing industry.